Accountability of immigration administration: Comparing crises in Norway, Denmark and Germany - Reichersdorfer, Johannes; Vrangbaek, Karsten; Christensen, Tom (2013)
Accountability can be conceptualized as institutionalized mechanisms obliging actors to explain their conduct to different forums, which can pose questions and impose sanctions. This article analyses different 'crises' in immigration policies in Norway, Denmark and Germany along a descriptive framework of five different accountability types: political, administrative, legal, professional and social accountability. The exchanges of information, debate and their consequences between an actor and a forum are crucial to understanding how political-administrative action is carried out in critical situations. First, accountability dynamics emphasize conventional norms and values regarding policy change and, second, formal political responsibility does not necessarily lead to political consequences such as minister resignations in cases of misbehaviour. Consequences strongly depend on how accountability dynamics take place. - Reproduced.
Keywords: Accountability; Immigration